2016
DOI: 10.2172/1371642
|View full text |Cite
|
Sign up to set email alerts
|

A Demonstration of Concrete Structural Health Monitoring Framework for Degradation due to Alkali-Silica Reaction

Abstract: Assessment and management of aging concrete structures in nuclear power plants require a more systematic approach than simple reliance on existing code margins of safety. Structural health monitoring of concrete structures aims to understand the current health condition of a structure based on heterogeneous measurements to produce high-confidence actionable information regarding structural integrity that supports operational and maintenance decisions. This ongoing research project is seeking to develop a proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…The standard test methods for determining the potential alkali-silica reactivity and for determination of the amount of time needed for concrete to change due to ASR are documented in ASTM C1567-13 and ASTM C1293-08b, respectively. Earlier reports by Mahadevan et al (2016Mahadevan et al ( , 2017 have studied various techniques and found them to be useful in damage detection. The VAM technique, investigated in detail in this report, shows particular promise in damage localization.…”
Section: Damage Evaluation Techniques For Monitoring Alkali-silica Rementioning
confidence: 99%
See 3 more Smart Citations
“…The standard test methods for determining the potential alkali-silica reactivity and for determination of the amount of time needed for concrete to change due to ASR are documented in ASTM C1567-13 and ASTM C1293-08b, respectively. Earlier reports by Mahadevan et al (2016Mahadevan et al ( , 2017 have studied various techniques and found them to be useful in damage detection. The VAM technique, investigated in detail in this report, shows particular promise in damage localization.…”
Section: Damage Evaluation Techniques For Monitoring Alkali-silica Rementioning
confidence: 99%
“…cast on December 21, 2015 and cured at Vanderbilt University. The details on casting and curing process of this concrete sample is discussed in detail the report by Mahadevan et al (2016). Figure 3 shows an image of the slab immediately after the mold was removed.…”
Section: Medium-sized Concrete Slab At Vanderbilt Universitymentioning
confidence: 99%
See 2 more Smart Citations
“…The framework will enable plant operators to make risk-informed decisions on structural integrity, remaining useful life, and performance of the concrete structure. The demonstration examples performed at Vanderbilt University using various techniques to assess the ASR degradation in controlled concrete specimens were reported in Mahadevan et al (2016).…”
Section: Introductionmentioning
confidence: 99%